Incidence of Post-Dural Puncture Headache in Post-Caesarean Section Patients with Spinal Anesthesia - Roro Lintang Suryani; Khofifah Tresno Putri; Dwi Novitasari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Delivery via caesarean section can lead to complications, one of which is Post-Dural Puncture Headache (PDPH). PDPH occurs within 3 days, with 66% of PDPH cases emerging within the first 48 hours post-puncture. Although PDPH manifestations may spontaneously recover within one week or after the leak seals, PDPH disrupts the care provided by the mother for her baby. The purpose of this study to determine the incidence of PDPH in post-caesarean section patients with spinal anesthesia at RSUD Kardinah Tegal City. This quantitative research utilized a descriptive design with a cross-sectional approach. The sample size was 35, selected through total sampling, with the sample characteristics being patients aged 17-45 years, ASA 1-2, and 48 hours post-operation. The data was collected through observations using the International Headache Society questionnaire (IHS). Data analyzed with univariate analysis aimed at seeing a picture of the frequency distribution of each variable. The results indicate that PDPH occurred in 2 respondents (5.7%) at 48 hours post-caesarean section with spinal anesthesia, and in 3 respondents (8.6%) at 72 hours. The highest percentage of PDPH incidence at RSUD Kardinah Tegal City was observed within the first 72 hours post-caesarean section with spinal anesthesia. Based on these results, it is evident that post-caesarean section patients can experience PDPH on the third day, which can be used for evaluation and care planning for these patients.